GÊNERO E PRISÃO: O ENCARCERAMENTO DE MULHERES NO SISTEMA PENITENCIÁRIO BRASILEIRO PELO CRIME DE TRÁFICO DE DROGAS: GENDER AND PRISON: THE INCARCERATION OF WOMEN IN THE BRAZILIAN PENITENTIARY SYSTEM FOR THE CRIME OF DRUG TRAFFICKING (REMUNOM, 2024)
The presente work consists of analyzing and listing the contradictions, criticisms about the relativization of the granting of house arres tto women in the Brazilian penitentiary system for the crime of drug trafficking. When paying attention to the involvement of womwn in criminal activities, it is possible to observe the participation of men in female criminal initiation. In this sense, women’ns behavior is seen as a result of affective or sexual association with criminal partners. Positioned exclusively as victims of the men around them, these women become accomplices in the crimes committed by their partners and eventually pay, througg incarceration, for behavion that is socially not recognized as feminine. However, observing the socioeconimic perspective of these women, being low income and low education, it can be understood that their participation in crime has been encouraged by the social environment in which they.Live, most often by their partners. It appears that, by being protected, as pregnant women in the Brazilian legal system that guarantees the right to freedom, many women have chosen to work in drug trafficking, in vien of the light punishment to which they are subjected, which emphasizes the early chidhood legal framework.